Značilnosti tlorisa stanovanj iz 20. stoletja (mariborska izkušnja) - Drozg, Vladimir (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
Comparing ground plans of apartments shows that their design and layout of rooms changed considerably during the last century. Some rooms were added, some others no longer exist, the size of rooms has also changed. There are three types of ground plans. One is from the beginning of the century, the other from the middle and the third from the end of the century. Changes of the ground plan can be linked to social characteristics of the bourgeois society, socialist system and the modern individualism and social wellbeing. Key words:
Keywords: Maribor; mesta; stanovanja; stanovanjske zgradbe; tlorisi